Psychosocial analysis of child abuse - Junco Supa, Jenny Elsa (2014)
This article presents a bibliographical and research review about the prevalence, characteristics, consequences and risk factors associated with violence against children and adolescents in private and public spaces. This study also develops and explains the forms of child abuse derived from other social problems in which direct caregivers and the State are involved. This problem is studied based on the theory of needs and risk factors. Furthermore, the family, school and community are involved in the prevention of this social problem.